2016
DOI: 10.15835/buasvmcn-hort:12173
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Terroir on Phenolic Composition of Red Grapes

Abstract: A rich content of phenolic compounds (anthocyans and tannins) is a fundamental technological condition for the obtaining of quality red wines -appreciated by increasing numbers of consumers, aware of the benefic health effects brought about by these biologically active compounds. The biosynthesis of phenols and their accumulation in the grape berries during ripening is influenced by a multitude of factors. In this study we focused on terroir and on the biological potential of the authorized red varieties for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…It was reported that these compounds of grape berries varied in different vineyards, and variations were also presented among cultivars being grown in the same vineyard for two consecutive years [21]. Additionally, agronomic strategies such as alteration of environmental conditions (light, temperature, mineral nutrition, and water management), application of elicitors, stimulating agents and plant activators have been employed to enhance the biosynthesis of polyphenols [18,22,23,24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…It was reported that these compounds of grape berries varied in different vineyards, and variations were also presented among cultivars being grown in the same vineyard for two consecutive years [21]. Additionally, agronomic strategies such as alteration of environmental conditions (light, temperature, mineral nutrition, and water management), application of elicitors, stimulating agents and plant activators have been employed to enhance the biosynthesis of polyphenols [18,22,23,24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…Temperature is known to strongly affect anthocyanin accumulation in grapes (Spayd et al, 2002;Yamane et al, 2006;Mori et al, 2007;Nicholas et al, 2011). At moderate growing temperatures (i.e., 20-25 • C) anthocyanin accumulation is promoted, while at relatively high temperatures (30-35 • C) anthocyanin accumulation is reduced, possibly because of a lower biosynthesis and/or higher rate of degradation (Yamane et al, 2006;Mori et al, 2007;Artem et al, 2016). Therefore, the temperature differences in the OV sub-regions may have contributed to the observed differences in anthocyanins ( Figure 6A).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous results indicating that seed tannin content varies with the seed number (Harbertson et al, 2002). Previous studies on the association of grape tannin content with terroir have yielded inconsistent results (Ferndandez-Marin et al, 2013;Artem et al, 2016). The effect of environmental factors such as temperature and water availability on tannins still remains unclear as contrasting results have been reported among studies indicating that the grape variety, as well as the interaction among various environmental factors affect tannin content (Cohen et al, 2008;Nicholas et al, 2011;Zarrouk et al, 2012;Genebra et al, 2014;Kyraleou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate temperatures during the night and day (15–25°C, respectively) promote the biosynthesis and accumulation of anthocyanins in the skins of the grape berries, while temperatures exceeding 35°C can decrease the accumulation of these chemicals through both the inhibition of biosynthesis pathways (107). and via the degradation of anthocyanins in grape skins (108, 109). Elevated and excessive temperatures can shorten phenological stages and impact bud break, flowering, véraison, ripening, maturity, and harvest, and affect wine quality.…”
Section: Environmental Conditionsmentioning
confidence: 99%